Microbial and filth contents of lettuce (Lactuca sativa L.) and upland kangkong (Ipomea acquatica Forssk) grown in selected production systems. - Arroyo, E. J. N. (Compendium of Human Ecology Researches in the Philippines, 2003)
An experiment was conducted to determine the microbial and filth contents of lettuce and upland kangkong grown in different production systems, namely: plain garden soil, organic, inorganic, and hydroponics. Study treatments included plain garden soil (control), plain garden soil with ammonium phosphate plus urea (inorganic), plain garden soil vermicompost plus carbonized rice hull (organic) and non-circulating hydroponics solution (hydroponics). Regardless of productions system, aerobic plate count (APC) was high in lettuce and upland kangkong, although the acceptable level was not exceeded. For the fecal coliform, the acceptable level was exceeded in lettuce grown in hydroponics. For upland kangkong, the acceptable level was exceeded in all samples. In terms of filth contents in lettuce, only one insect fragment was found in plain garden soil, inorganic, hydroponics, and none in organic. In upland kangkong, insect fragments were present regardless of production system. The study showed that microbial count of the growing media was still within the acceptable level at harvest. The same observed in harvested upland kangkong and lettuce except for those grown in hydroponics while filth contents were high.